A DNA Origami Mechanical Device for the Regulation of Microcosmic Structural Rigidity. Issue 41 (13th September 2017) - Wan, Neng; Hong, Zhouping; Wang, Huading; Fu, Xin; Zhang, Ziyue; Li, Chao; Xia, Han; Fang, Yan; Li, Maoteng; Zhan, Yi; Yang, Xiangliang
Abstract: DNA origami makes it feasible to fabricate a tremendous number of DNA nanostructures with various geometries, dimensions, and functionalities. Moreover, an increasing amount of research on DNA nanostructures is focused on biological and biomedical applications. Here, the reversible regulation of microcosmic structural rigidity is accomplished using a DNA origami device in vitro. The designed DNA origami monomer is composed of an internal central axis and an external sliding tube. Due to the external tube sliding, the device transforms between flexible and rigid states. By transporting the device into the liposome, the conformational change of the origami device induces a structural change in the liposome. The results obtained demonstrate that the programmed DNA origami device can be applied to regulate the microcosmic structural rigidity of liposomes. Because microcosmic structural rigidity is important to cell proliferation and function, the results obtained potentially provide a foundation for the regulation of cell microcosmic structural rigidity using DNA nanostructures. Abstract : A DNA origami monomer is constructed with a central axis and an external sliding tube, of which the linear motion is regulated by fuel and antifuel strands. Significantly, when the flexible dimer reacts with the fuel strand, it undergoes conformational change and becomes rigid increasing the structural rigidity of liposomes. This work provides an idea to regulate cell's rigidity in future research.